Learning Power in Practice : A Guide for Teachers - Crick, Ruth Deakin (Paul Chapman Publishing, 2006)
This book tells you all about the acclaimed effective lifelong learning inventory research programme (ELLI), explains how it works in the classrom and shows you how to find your own answers to these questions. The Book offers a wealth of practical suggestions for improving the learning power of all the children in your class.